Circuits of architecture and urban planning : Professional ethos and the internationalization of small architectural offices - Kettunen, Erja; Oinas, Päivi; Kalliomäki, Helka (Wiley, 2021)
Although the production of the built environment is increasingly globalized, and architecture and urban planning (AUP) professionals are known to be the key carriers of mobile ideas, the internationalization of small owner-centred architectural offices has gained little academic attention, compared to the large consultancies that dominate the global market. We bring together the literature on the circuits of urban planning ideas, the international movement of AUP firms and professional ethoses to explore the internationalization of small AUP offices. Using interview data from Finnish offices, we investigate the ‘what, where, why and how’ and find that they have entered specific geographically delimited AUP circuits demarcated by type of project. We contribute to the literature by identifying motives characteristic of small offices guided by professional ethoses suited to the circuits where they internationalize. Their ethoses may evolve in time and space, as they operate in new circuits. We propose that ethos–circuit coherence may contribute to the successful internationalization of small architectural offices. The findings open avenues for further research on professional ethos not only of architects but also other internationally operating professionals, as it may guide their decisions by other than a narrowly conceived profit motive.
Keywords: circuits of architecture and urban planning; Finnish architecture; motives of internationalization; professional ethos; small architectural offices; fi=Aluetiede|en=Regional Studies|